Therapeutic Potential of Perillaldehyde in Ameliorating Vulvovaginal Candidiasis by Reducing Vaginal Oxidative Stress and Apoptosis - Lei Chen; Fei Wang; Su Qu; Xiaona He; Yongxin Zhu; Yi Zhou; Kunlong Yang; Yong-Xin Li; Man Liu; Xue Peng; Jun Tian (Antioxidants, 2022)
Vulvovaginal candidiasis (VVC) is one of the most frequent diseases induced by Candida albicans (C. albicans) during pregnancy, which results in enormous pain to women and their partners in daily life. Perillaldehyde (PAE), a natural monoterpenoid, has significant anti-microbial, anti-inflammatory and anti-oxidation effects. Reactive oxygen species (ROS) are key factors for the host to resist the invasion of fungi. However, excess ROS can cause additional damage independent of the pathogen itself, and the mechanism of ROS in VVC has not been investigated. In this murine study, we revealed that C. albicans infection increased the expression of NADPH oxidase 2 (NOX2) and the content of malonaldehyde (MDA). C. albicans inhibited the activity of antioxidant enzymes in the vagina, including superoxide dismutase (SOD), Catalase (CAT), glutathione peroxidase (GSH-PX) and heme oxygenase (HO-1), which were returned to normal levels after treatment with PAE. Furthermore, PAE inhibited the activities of Keap1 and promoted Nrf2 transfer from cytoplasm to nucleus, which were mediated by excessive accumulation of ROS in the VVC mice. In this study, we also indicated that PAE inhibited the apoptosis of vagina cells via Caspase 9- Caspase 7-PARP pathway and prevented the release of IL-1ꞵ in VVC mice. In summary, this study revealed that the treatment of VVC in mice with PAE might be mediated by inhibition of ROS, and established the therapeutic potential of PAE as an antifungal agent for the treatment of VVC.